Seasonal variation, sources, and risk assessment of PM2.5-bound PAHs in Nantong, China: A pre- and post-COVID-19 case study - Guo, Xinying; Chen, Feng; Lu, Juan; Zhang, Weibing (Frontiers in Environmental Science, 2022)
Between 2018 and 2022, a total of 231 PM2.5 samples were collected in Nantong, China and analyzed online for 16 US EPA PAHs utilizing a variety of analytical methodologies, including high-performance liquid chromatography data analysis, principal component analysis, and characteristic ratio analysis. The seasonal variation and pollution characteristics of 16 PAHs in PM2.5 over a long period in Nantong, China were analyzed, and correlations and traceability changes with a variety of emission sources were established with different emission sources. Additionally, health assessment models for BaP equivalent concentration, daily exposure dose, lifetime excess risk of cancer, and life expectancy loss were constructed for various ages and genders. The results indicated that the total number of days with BaP concentrations less than the national limit standard of 1.0 ng/m3 was 60.17% (139/231), with rates of 25.40%, 35.71% and 94.05% from 2019 to 2021, respectively; the total concentration range of 16 PAHs demonstrated a downward trend, but pollution was relatively severe in winter. The seasonal variation showed winter > autumn > spring > summer. The detection rates of 4 and 5 rings were generally high and fluctuated between dropping and increasing. Principal factor analysis and characteristic ratio traceability analysis indicated that PAHs pollution is primarily caused by local coal-fired sources and traffic emissions, with a new trend of biomass combustion. Furthermore, BaP remains the primary contributor to carcinogenic factors, and the health risk is higher in females than in males, and in adults than in children. A low level of PAHs in the air may have health benefits. Traffic control and flow restrictions, as well as production restrictions, are all part of Nantong's COVID-19 pandemic prevention and control policies. These policies contributed to PAH risk prevention and control, as well as pollution reduction.